Assessment of the effectiveness and efficacy of seed villages in India - Bhuvana, Narayana Rao; Dominic, Ditty Maria; Mittal, Nimisha; Sulaiman V, Rasheed; Puskur, Ranjitha; Tenneti, Suchaita (CGIAR Initiative on Seed Equal, 2023)
With limited arable land and increasing population, India faces a unique challenge in ensuring food and nutrition security, especially as climate change intensifies. Access to high quality seeds of improved crop varieties is critical for enhancing agricultural production and productivity and ensuring food security. But as access to such quality seeds from the formal sector is limited, many of the smallholder farmers are forced to rely on farmer-saved seeds. The Government of India introduced the Seed Village Programme (SVP) during the early 1960s to enable replacement of existing local varieties and farmer-saved seeds with new high-yielding varieties by empowering local communities to produce and distribute quality seeds. Since then, several other organisations have adopted the SVP and promoted quality seed production.